If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + y)(x + -1y) = 44 Multiply (x + y) * (x + -1y) (x(x + -1y) + y(x + -1y)) = 44 ((x * x + -1y * x) + y(x + -1y)) = 44 Reorder the terms: ((-1xy + x2) + y(x + -1y)) = 44 ((-1xy + x2) + y(x + -1y)) = 44 (-1xy + x2 + (x * y + -1y * y)) = 44 (-1xy + x2 + (xy + -1y2)) = 44 Reorder the terms: (-1xy + xy + x2 + -1y2) = 44 Combine like terms: -1xy + xy = 0 (0 + x2 + -1y2) = 44 (x2 + -1y2) = 44 Solving x2 + -1y2 = 44 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y2' to each side of the equation. x2 + -1y2 + y2 = 44 + y2 Combine like terms: -1y2 + y2 = 0 x2 + 0 = 44 + y2 x2 = 44 + y2 Simplifying x2 = 44 + y2 Reorder the terms: -44 + x2 + -1y2 = 44 + y2 + -44 + -1y2 Reorder the terms: -44 + x2 + -1y2 = 44 + -44 + y2 + -1y2 Combine like terms: 44 + -44 = 0 -44 + x2 + -1y2 = 0 + y2 + -1y2 -44 + x2 + -1y2 = y2 + -1y2 Combine like terms: y2 + -1y2 = 0 -44 + x2 + -1y2 = 0 The solution to this equation could not be determined.
| 20-(x+8)=6x-2 | | 4y-7-2y+6=0 | | 10x+28=6x+12 | | 10x-7=40x+17 | | 11(3+y)=5(2y+8) | | 3x^2+12x+48=0 | | x^2=2(4-x) | | 24=4(x+4) | | 9x-4y=-37 | | x^2+4(x-3)=0 | | 3(x^2+2x)=9 | | 3x+(x-2)+(2x-1)=18 | | 1-5x+6x^2=0 | | 5-3x-2x^2=0 | | -5y+6=-4(2y+3) | | x+3=2x^2 | | y=8-12+2y | | 5x+20x=1320 | | 5x-20x=1320 | | -(a-5)+7=-(8+3a) | | -4(1+2n)=-2(n-1) | | 90=10(x+16) | | x+(x-2)= | | 17x=-12 | | 5(v-7)=-39+3v | | 6(x+1)=-5x-5 | | 35=10b+50 | | 2x+4(2x+7)=3(2x+4) | | -(3+2x)=17 | | 4b^2=9 | | 6-(-6b-3)=-3b-27 | | -32-5x=2(4x-6)-7 |